2022
DOI: 10.35916/thmr.v4i1.59
|View full text |Cite
|
Sign up to set email alerts
|

Fungicidal Effects of Chloroform Extract of Red Galangal (Alpinia purpurata (Vieill.) K. Sch) on the Growth of Trichophyton rubrum

Abstract: Trichophyton rubrum is the most common causative agent of anthropophilic dermatophytosis worldwide. Treatment of dermatophytosis can use natural ingredients. In Indonesia, several medicinal plants have been used, one of which is red galangal (Alpinia purpurata (Vieill.) K. Sch). This study aims to determine the effectiveness of red galangal rhizome chloroform extract on the growth of Trichophyton rubrum. This study is a True Experiment study with Posttest Only With Control Group Design consisting of 8 treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The lectins from A. purpurata inflorescence showed antileukemia potential ( Brito et al, 2023 ). Previous studies showed the potential effects of A. purpurata rhizome against fungal infection ( Azizah et al, 2022 ) and cancer ( Palanirajan et al, 2022 ).…”
Section: Distribution Taxonomy and Ethnopharmacological Usesmentioning
confidence: 99%
“…The lectins from A. purpurata inflorescence showed antileukemia potential ( Brito et al, 2023 ). Previous studies showed the potential effects of A. purpurata rhizome against fungal infection ( Azizah et al, 2022 ) and cancer ( Palanirajan et al, 2022 ).…”
Section: Distribution Taxonomy and Ethnopharmacological Usesmentioning
confidence: 99%